Subjetividade e intimismo em a poesia em pânico, de Murilo Mendes - Moura, Luana Eydsan Silva de (2019)
In A poesia em pânico (The Poetry in Panic), a book published in 1937, Murilo Mendes, the poet of tensions and conciliatory paradoxes, is not only the author who follows the book of modern poetry, but presents an intimate lyricism by paths of confessional subjectivity and eroticism, which differs from his other books. These elements come, in this work, marked by a poetic persona in panic, that experiences the sacred and the profane in constant tensions. The objective of this work is to investigate, through the analyzes of the poems, the aesthetic and historical elements that conduct Murilo Mendes to conceive a so differentiated diction in A poesia em pânico (The Poetry in Panic), with a subjective and intimate perspective quite different from that presented in the books previous and subsequent of the author. The work is justified, therefore, the question raised by him has not yet been sufficiently studied by the critics of Murilo Mendes, who, in general, neither turn themselves to the intimacy and subjectivity in the poet, nor in A poesia em pânico (The Poetry in Panic). In order to base our research, we use some theories of the poetic persona, such as Hugo Friedrich's Estrutura da lírica moderna (Modern Structure of lyrical), which defends the thesis of the depersonalization of the poetic persona in modernity. Contrary to this criticism, we use the positions of, among others, Michel Hamburger, in A verdade da poesia (The truth of poetry), to show that, although modern, Murilo Mendes could also be intimate and confessional. We also rely on the studies of Georges Bataille, which is essential to understand the connection between the sacred and the profane explored by Murilo Mendes in several poems of the book. Thus, taking into consideration what we have studied and pointed out, we confirm our hypothesis that A poesia em pânico (The poetry in panic) is a book in which subjectivity is much more intimately constituted than in others, where we find a subject who can not commune with the sacred, because it wants to strengthen its individuality through sin that isolates it from God, becoming more individual, more subjective. On the other hand, intimacy will also be thought of in the path of eroticism, evoked always with its sacred face, because from this erotic-sacral fusion emanates the ecstatic effect, that is, poetic ecstasy, the highest degree of emotionality of sacred poetry.